PERTUMBUHAN DAN HASIL PADI SAWAH ORGANIK DENGAN MENGGUNAKAN PUPUK KANDANG SAPI DAN AZOLLA - Mujiyo Mujiyo; Bambang Hendro Sunarminto; Eko Hanudin; Jaka Widada (Caraka Tani: Journal of Sustainable Agriculture, 2015)
Farmyard manure and azolla are potential sources of organic fertilizer in organic paddy field. This study aimed to determine the effect of using farmyard manure and azolla on growth and yield of rice crop. The research method was field trial in an organic paddy field, Sukorejo Village, Sragen, Indonesia. Experimental design which used was a completely randomized block design with 9 kinds of treatment which are repeated in 3 blocks. These kind of treatments were the using of farmyard manure, azolla fertilizer, azolla inoculum, and the combinations which is based on the fulfillment of nutrient requirements of 120 kg N ha-1. Farmyard manure significantly increased the fresh weight of biomass (two-way ANOVA F = 3.13 p < 0.05), the weight of grains per panicle (two-way ANOVA F = 3.36 p < 0.05) and dry grain harvest (two-way ANOVA F = 3.71 p < 0.05). Azolla fertilizer significantly increased the plant height (two-way ANOVA F = 2.93 p < 0.05). Meanwhile azolla inoculum did not give significant effect on all parameters (both growth and yield). Dry grain harvest has very significant correlation with plant height (0.68**); fresh weight of biomass (0.79**); weight of grains per panicle (0.61**); and grain weight of 1,000 seeds (0.48*). The result of F test and correlation analysis showed that farmyard manure significantly increases the dry grain harvest through its role on increasing the weight of fresh biomass and grain weight per panicle. Azolla fertilizer also significantly increased the dry grain harvest through its role on increasing the plant height. However, the effect of Azolla fertilizer to increase the dry grain harvest was weaker than farmyard manure.